Effect of Different Moisture Conservation Practices on Soil Profile Recharging and Water Use Efficiency in Silvipastoral System - Kumar, Sanjiv; Yadav, M.P. (Indian Journal of Agroforestry, 2020)
Field experiments were carried out during two Kharif consecutive years 1997 and 1998 at National Agricultural Technology Project Hazaratpur Firozabad (UP). Four in-situ moisture conservation practices viz; shallow ploughing (SP), SP + compartmental bunding (CB), deep ploughing (OP) and OP + CB were applied in one-year-old Leucaena spp plantation. Dinanath grass was sown after ploughing and compartmental bundings done just after sowing of Dinanath grass. In general, the moisture extraction pattern, moisture use day-1 and seasonal consumptive use of water was recorded high in deep ploughing along with compartmental bunding treatment. The moisture extraction from lowest depth (60-90cm) was 5.4, 5.9, 6.2, and 6.7 per cent in 1997 and 4.6, 5.2, 5.7, and 6.1 per cent in 1998 respectively.